1999
DOI: 10.1002/(sici)1096-9071(199909)59:1<1::aid-jmv1>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

A two dose combined hepatitis A and B vaccine in Chinese youngsters

Abstract: This open, randomized study was conducted in healthy Chinese youngsters, aged between 10 and 19 years to compare the reactogenicity and immunogenicity of two vaccines: the combined vaccine against hepatitis A and B was administered in a two-dose schedule with the profile of the corresponding monovalent vaccines, while the concomitant vaccine was administered also on a two-dose schedule but simultaneously in opposite arms. All vaccinees had antibodies against hepatitis A (anti-HAV) after the 2-dose administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Five to 10 years after primary vaccination, all children (100%) remained seropositive for anti-HAV [10,15,47,53]. After the second dose (month 7), GMC was 3701-14790.1 mIU/ml [10,15,38,41,47,48,[50][51][52][53][54]. Long-term follow-up data showed that GMC decreased over the years, but remained above the seropositivity cut-off up to 10 years follow-up [10,15,47,53].…”
Section: Ambirix Tmmentioning
confidence: 98%
See 4 more Smart Citations
“…Five to 10 years after primary vaccination, all children (100%) remained seropositive for anti-HAV [10,15,47,53]. After the second dose (month 7), GMC was 3701-14790.1 mIU/ml [10,15,38,41,47,48,[50][51][52][53][54]. Long-term follow-up data showed that GMC decreased over the years, but remained above the seropositivity cut-off up to 10 years follow-up [10,15,47,53].…”
Section: Ambirix Tmmentioning
confidence: 98%
“…The most reported solicited systemic reactions were fever, fatigue, and headache (Table 12). The percentage of participants experiencing unsolicited AEs ranged between 0% and 30.2% [41,48,50,54]. The kind of unsolicited event was not reported.…”
Section: Ambirix Tmmentioning
confidence: 98%
See 3 more Smart Citations